Olfactory Plasticity: Variation in the Expression of Chemosensory Receptors in Bactrocera dorsalis in Different Physiological States - Jin, Sha; Zhou, Xiaofan; Gu, Feng; Zhong, Guohua; Yi, Xin (Frontiers in Physiology, 2017)
Changes in physiological conditions could influence the perception of external odors, which is important for the reproduction and survival of insect. With the alteration of physiological conditions, such as age, feeding state, circadian rhythm and mating status, insect can modulate their olfactory systems accordingly. Gustatory, ionotropic and odorant receptors (GR, IR and ORs) are important elements of the insect chemosensory system, which enable insects to detect various external stimuli. In this study, we investigated the changes in these receptors at the mRNA level in Bactrocera dorsalis in different physiological states. We performed transcriptome analysis to identify chemosensory receptors: 21 IRs, 12 GRs and 43 ORs were identified from B.dorsalis antennae, including all previously known chemoreceptors in B. dorsalis and a few more. Quantitative real-time polymerase chain reaction analysis revealed the effects of feeding state, mating status and time of day on the expression of IR, GR and OR genes. The results showed that expression of chemosensory receptors changed in response to physiological states, and these changes were completely different for different types of receptors and between male and female flies. Our study suggests that the expression of chemosensory receptors changes to adapt to different physiological states, which may indicate the significant role of these receptors in such physiological processes.